Simulation of partial discharge within a void under square waveform applied voltage - Illias, Hazlee Azil; Bakar, A.H.A.; Mokhlis, Hazlie; Tunio, M.A.; Chen, G.; Lewin, P.L.; Ariffin, A.M. (2012)
Partial discharge (PD) activity within a void in a dielectric material is influenced by many factors. One of the factors is the applied voltage waveform on the material. In this paper, a two-dimensional (2D) model of a cylindrical void in polyethylene layers has been developed using finite element analysis (FEA) software. The model was used to simulate PD activity in the void under square waveform applied voltage. The obtained simulation results were compared with the measurement results from literature. It was found that both results are within reasonable agreement but with only slight disagreement. From comparison, critical parameters from the model affecting PD activity under square waveform applied voltage were identified; they include the inception and extinction voltages and electron generation rate. This finding may increase an understanding of PD behaviour within a void in a dielectric material under square waveform applied voltage.